Implementation of the PAKEM Model as an Effort to Improve the Learning Outcomes of Islamic Religious Education and Ethics in Primary Schools - Sari, Sindi Antika; Taqwa, Taqwa; Hisbullah, Hisbullah; Widiantari, Ketut (Educational Journal of Learning Technology, 2026)
The ability to read the Qur’an accurately and correctly is a crucial competency for students in madrasah ibtidaiyah. This study aims to describe the application of the Tahsin method in improving the ability to read the Qur’an. The research method employed is a descriptive qualitative approach, utilising data collection techniques that include observation, interviews, and documentation. The study’s results showed that the Tahsin method was implemented through teacher-led example Reading, student imitation, correction of Reading errors, and repeated exercises. This method is practical for enhancing the accuracy of makhraj, applying tajweed rules, and improving students’ fluency in reading the Qur’an. These findings demonstrate that the Tahsin method is effective in fostering optimal Qur’an Reading skills from an early age.